Teori Dalil Hukum Rujuk - Laila Syuhada; Mhd. Amar Adly; Heri Firmansyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This paper aims to find out how the definition of rujuk, how the himpuna of the arguments about rujuk, how the munasabah of the arguments between the arguments about rujuk and how the concept of rujuk according to the compilation of Islamic law. This research is a library study (library resecarh). Primary data sources are obtained by reading the literature related to the discussion of rujuk. The results of the study show that rujuk is an act or utterance of the husband wanting to return to his spouse while the arguments for rujuk are found in the Qur'an and Hadith, there is a relationship between the arguments with other arguments related to rujuk, and the concept of rujuk according to the compilation of Islamic law is in line with the laws contained in the Qur'an and Hadith.